Pemanfaatan Peribahasa Lokal sebagai Strategi Pembelajaran Bahasa Indonesia pada Siswa Kelas V SD Negeri Mardekaya 2 Kota Makassar - Sitti Fadilah Ilham; Andi Adam; Ratnawati Ratnawati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to describe the use of local proverbs as a strategy for learning Indonesian in elementary school children. This type of research is qualitative in this study there are types and approaches to research, place and time of research, data and data sources, research procedures, data collection techniques, research instruments, data analysis techniques and definitions of terms. Data Collection Techniques Observation/observation of activities is carried out by researchers by directly observing the learning process carried out by teachers and students using observation sheets. Research interviews use interviews with teachers and students to use interview guidelines that have been prepared by research related to the use of local proverbs in schools. Documentation of this study uses documentation techniques in collecting data. This technique aims for researchers to obtain documents in the form of a list of local proverbs, several uses of local proverbs and photos of the learning process. Data Analysis Techniques Data analysis techniques aim to analyze data that has been collected in research. After data from the field has been collected and arranged systematically, the next step is for the author to analyze the data. The results of the study on the use of local proverbs in learning Indonesian are shown in the aspects of language, culture, character and cognitive. The Language aspect is found in student activities in listening skills, namely listening to stories containing the proverb Reso temmamgingngi. The Cultural Aspect is found in the existence of learning activities in the use of local proverbs as a preservation of culture, especially in South Sulawesi. The Cognitive Aspect is found in student understanding related to the knowledge or meaning of each local proverb used. The Character Aspect is found in the activity of instilling character values ​​in local proverbs.